Effect ginger (Zingiber officinale Rosc.) extract addition on antioxidant activity, phenol total content, overrun, sensory, and shelf life of Ice Puter [Efek penambahan ekstrak jahe (Zingiber officinale Rosc.) terhadap aktivitas antioksidan, kandungan total fenol, overrun, sensori dan masa simpan es puter] - Al-Baarri, Ahmad Ni'matullah; Dewi, Swastika; Putra, Hega Bintang Pratama; Mulyani, Sri; Legowo, Anang Mohamad; Ananda, Azzahra Damia; Handaruwulan, Azzahra Salsabila; Putri, Jessica Aryani (Jurnal Teknologi & Industri Hasil Pertanian, 2025)
Ginger is known to contain various bioactive compounds, including phenolics (gingerol, shogaol, paradol). Several studies have shown that ginger extract is often added to ice puter to obtain healthier food product. Therefore, this study aims to analyze the result of adding ginger (Zingiber officinale Rosc.) extract with different concentration on antioxidant activity, total phenol content, overrun, hedonic test, and shelf life of ice puter. The study were conducted from November 2023 - February 2024 at Diponegoro University. The research design was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, leading to a total of 20 experiment units. The experiment was conducted by adding ginger extract with different concentrations, namely P1 (0%), P2 (0.5%), P3 (1%), and P4 (1.5%). Shelf-life prediction was carried out with 3 replicates, leading to 9 experiment units for different storage temperatures (-5 °C, -18 °C, -22 °C). The sample selected from the hedonic test, P1 (0.5%) was evaluated for 28 days with changes in parameters of free fatty acid and emulsion stability. This result shows that the addition of ginger extract at various concentrations had significant effect on overrun, while, treatment P1 and P2 did not have significant effect on color and aroma. The addition of ginger extract increased antioxidant activity and total phenol content. In addition, the ice putter added with 0.5% ginger extract was the ice putter most preferred by panelists and had a shelf life of 210 days at -22°C, based on changes in free fatty acid during storage.